Copper 1, 19‐Diaza‐21, 24‐dicarbacorrole: A Corrole Analogue with an N−N Linkage Stabilizes a Ground‐State Singlet Organocopper Species. (25th June 2020) - Basumatary, Biju; Hashiguchi, Ikuho; Mori, Shigeki; Shimizu, Soji; Ishida, Masatoshi; Furuta, Hiroyuki
Abstract: A copper complex of a heterocorrole analogue with an N–N linkage, 1, 19‐diaza‐21, 24‐dicarbadibenzocorrole (Cu‐5 ), was successfully synthesized via oxidative metalation–cyclization of a tetrapyrrolic precursor. The N–N linkage in the skeleton of Cu‐5, which serves as a mediator of π‐electron delocalization, features an 18π aromatic system. The electronic structure of Cu‐5 is best described as a ground‐state singlet species stabilized by the distinct NNCC coordination core. This finding shows how the ligand's design can be used to modulate the Cu 3 d x 2 - y 2 orbital energy, thereby making such compounds invaluable for copper‐based catalytic applications. Abstract : More confusion? ! In the copper complex of dicarbacorrole (referred to as N^Norrole), the lone pair electrons in the N(sp 2 )–N(sp 2 ) linkage in the circuit played a crucial role in the global 18π conjugation circuit due to Hückel aromatic stabilization. The resulting NNCC coordination core in copper facilitated the upshifting of the Cu 3d x 2– y 2 ‐dominant orbital to afford a singlet organocopper species.